The Institutional Features of the Judicial Oversight on the Legitimacy of the "Pre-Judicial" Phase of the Proceedings for Confiscation of Property of Illicit Origin - Markosyan, Tigran; Hovhannisyan, Vahe (Bulletin of Yerevan University C: Jurisprudence, 2023)
The legal proceedings for confiscating property of illicit origin represent a novelty in Armenian legal system, and the study of both its comprehensive and individual issues hold significant theoretical and practical importance.Based on international documents, domestic legislation, and jurisprudence, the authors present an analysis of the general characteristic of the confiscation of property of illicit origin, as well as discuss several practical issues in the existing tools for management of the legitimacy of its "pre-trial" stage. Namely, the necessity for proper judicial oversight of acts, including actions and omissions that fall outside the scope of current oversight mechanisms, its implementation peculiarities, including consequences of recorded infringements are highlighted and as a result, the need for legislative regulations of such issues is raised.In the article, the authors present several scientific and practical conclusions, such as the need to establish on a legislative level the scope and conditions for oversight of the legitimacy of the decisions, actions, and omissions of the competent authority in the "pre-judicial" stage of the confiscation of property of illicit origin. As a result, it can be stated that the conclusions presented in the article can serve as an indication for the further development of legal practice and existing regulations.
Keywords: civil confiscation; proceedings for confiscation of property of illicit origin; in rem; right to property; legitimacy; judicial oversight; direct appeal; “deferred” appeal